The effect of calcium hydroxide placement on pH and calcium concentration in periapical environment: An in vitro study - Behnaz Barekatain; Seyed Mohsen Hasheminia; Elham Shadmehr; Zeinab Attary (Wolters Kluwer Medknow Publications, 2012)
Aims: Comparing the calcium concentration and pH levels of Ca(OH) 2 medicament placing in pulp chamber and root canal. Materials and Methods: Ninety-nine extracted human mandibular second premolars were instrumented to size #40 k file. Nine teeth served as the control group and the remaining teeth were assigned into two groups. Group 1-Ca(OH) 2 was placed in the dried pulp chamber, while root canals remained wet with normal saline; group 2-Ca(OH) 2 was placed in dried root canals. In control group, canals remained wet without medication. Each group was divided into 3 sub-groups of 15 teeth in which pH and calcium concentration were measured in three intervals of 2 days, 1 week, and 2 weeks by pH meter and atomic absorption spectrometer system, respectively. Findings were assessed using Kruskal-Wallis and t-test. Results: At 1 and 2 weeks, the calcium concentration had increased without being significantly different from Ca(OH) 2 placed either in the root canal or in the pulp chamber. Ca(OH) 2 placed in the pulp chamber or root canal provided similar pH values (P=0.362). Conclusions: Placing Ca(OH) 2 in pulp chamber is as effective as placing it in the root canal.